PVC failure modelling through experimental and digital image correlation measurements (Fracture and Structural Integrity, 2022)
This paper analyses industrial PVC sheets structural integrity assessment widely used for different ranges of industrial applications. We investigated combined approaches focused on fracture toughness assessment to predict PVC mechanical behavior against failure. We ran a series of tests on tensile and single-edge notched samples at various crosshead speeds on a tensile test machine. PVC sheets' stress intensity factors were evaluated using both theoretical and experimental approaches to model crack growth. In the experimental procedure, we used the digital image correlation (DIC) method. We also developed a semi-empirical model to predict crack length over time. Furthermore, we proposed that the crack growth rate and stress intensity factor were satisfactorily correlated at all crosshead speeds and that the crack growth rate could be represented using a power-law model. In pre-cracked PVC specimens, the results showed that crack growth appears to be influenced by crosshead speed.
Keywords: Crack growth; stress intensity factor; strain rates; DIC; PVC